The Role of Family and School Environments in Early Childhood Vegetable Consumption Practices from a Sociocultural Perspective - Tri Handayani; Diah Wahyuningsih (Golden Ratio of Data in Summary, 2026)
Vegetable consumption in early childhood is a crucial factor influencing children’s cognitive and physical development. For kindergarten-aged children (4–6 years), vegetable intake affects not only their physical health but also their mental well-being, intelligence, immune system, and social interactions with peers. Research by the Indonesian Ministry of Health indicates that 93.5% of children in Indonesia still have insufficient vegetable consumption. This percentage is based on a survey showing that consuming fewer than five servings of vegetables per day is categorized as low. This study aims to identify the role of family and school environments in shaping vegetable consumption practices among early childhood students at PAMARDI PUTRA Kindergarten from a sociocultural perspective using a quantitative model. The population was selected through proportionate stratified random sampling, consisting of 17 students and their parents, as well as 3 teachers. Data were collected through questionnaires distributed to each participant and anthropometric measurements to determine Body Mass Index (BMI) as an indicator of students’ nutritional status. The results show that the coefficient of determination (R²) indicates that mothers’ attitudes explain approximately 98.6% of the variation in children’s nutritional status, while teachers’ attitudes account for 75.3%. The remaining variation is influenced by other factors, such as children’s behavior, family economic conditions, availability of time for mothers and teachers, genetics, and household eating culture.